A study of male fashion: A preliminary assessment of industry practice - Midgley, David F. (Cranfield School of Management, 1972)
A From 20+ interviews with retailers, manufacturers, and other members of the menswear industry, the following major points have been extracted. 1 Selection of garments and demand forecasting is carried out by a single function - a merchandise function. 2 Style and colour are selected on the basis of experienced judgement. 3 Influence on colours is perceived as predominantly from the Continent, whilst design influence is mainly from the London high fashion and boutique industry. 4 Demand estimation is achieved by extrapolation of past sales trends, sometimes coupled with trials of new styles in selected outlets. 5 Forecasting demand is seen as a problem, the more fashionable the market the greater the problem. 6 Most retailers sell both to a fashionable and a conventional. mass market 7 Within these markets the consumers are seen as: (i) becoming more fashion conscious, particularly the young; and (ii) wearing more casual and informal garments. 8 B The evidence gathered on these points supports the contention that the fashion process is similar. to the theory of the diffusion of ililovation. The supporting evidence falls in two main categories. 1 Styles originate and filter into the mass market in a manner consistent with the tenets of diffusion theory. The characteristics of consumers in the various market segments match those of the various categories embodied in the theory. C In short, this small study encourages us to continue along the line of research described in Report No 1.